2013
DOI: 10.1002/pmic.201200380
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the nuclear proteome of a dehydration-sensitive cultivar of chickpea and comparative proteomic analysis with a tolerant cultivar

Abstract: Water deficit or dehydration hampers plant growth and development, and shrinks harvest size of major crop species worldwide. Therefore, a better understanding of dehydration response is the key to decipher the regulatory mechanism of better adaptation. In recent years, nuclear proteomics has become an attractive area of research, particularly to study the role of nucleus in stress response. In this study, a proteome of dehydration-sensitive chickpea cultivar (ICCV-2) was generated from nuclei-enriched fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…Another enzyme, glyoxalase, involved in the detoxification of R-oxoaldehydes, was also up-regulated in the tolerant variety. The lack of induction of major ROS catabolic enzymes may lead to hypersensitivity of plants during dehydration-induced oxidative stress (Subba et al 2013). The up-regulation of glyoxylate was also observed in rice root tissue in response to cold treatment (Lee et al 2009).…”
Section: Enzymatic Reactive Oxygen Species Scavengersmentioning
confidence: 77%
“…Another enzyme, glyoxalase, involved in the detoxification of R-oxoaldehydes, was also up-regulated in the tolerant variety. The lack of induction of major ROS catabolic enzymes may lead to hypersensitivity of plants during dehydration-induced oxidative stress (Subba et al 2013). The up-regulation of glyoxylate was also observed in rice root tissue in response to cold treatment (Lee et al 2009).…”
Section: Enzymatic Reactive Oxygen Species Scavengersmentioning
confidence: 77%
“…However the outcome is affected by genotypic divergence, organ and tissues, developmental stages besides different environmental cues. The proteomics studies revealed the influence and efficacy of such approach to distinguish the landraces, populations, varieties and even species (Jaiswal et al, 2013;Subba et al, 2013).…”
Section: Comparative Tuber Proteome Profilingmentioning
confidence: 99%
“…Based on an oligonucleotide microarray containing 6,164 unigenes, Wang et al (2012) reported a large number of unigenes differentially expressed in the root and leaf under drought stress. The proteomics approach has also identified abiotic stress-responsive proteins in chickpea (Pandey et al 2006;Subba et al 2013). Recently, based on phenotyping and genotyping of two intra-specific recombinant inbred line populations, at least nine quantitative trait locus (QTL) clusters for drought tolerance traits have been identified (Varshney et al 2014).…”
Section: Introductionmentioning
confidence: 99%